Implementation of Field Study as an Active Learning Strategy in a Tourism Geography Course - Partini, Dwi; Asep; Helmi, Dewilna (Journal of Geography Science and Education, 2025)
Active learning is a crucial approach for creating dynamic and application-oriented learning environments. One relevant active learning method in Tourism Geography is the field study. This article aims to analyze the implementation of field study as an active learning strategy to enhance students’ understanding and engagement. Employing a mixed-methods approach, the study involved 30 students and one course instructor in a field activity at Rumah Pohon Waai, Central Maluku, Indonesia. Quantitative data were collected through questionnaires, tests, and evaluations of final reports, while qualitative data were obtained through observations, interviews, and student reflections. The findings indicate that the field study significantly improved conceptual understanding, analytical skills, as well as students’ motivation and participation in the Tourism Geography course. The article recommends broader adoption of field studies within experiential learning practices in higher education.